Longitudinal dynamics of wing in ground effect craft in waves - Adhynugraha, Muhammad Ilham (Cranfield University, 2017)
An assessment of the longitudinal motion of a hybrid configuration called the aerodynamically alleviated marine vehicle (AAMV) with the presence of waves, is demonstrated in the thesis. The development of this type of vehicle requires a mathematical framework to characterise its dynamics with the influence of external forces due to the waves’ motion. An overview of the effect of waves towards the models of dynamics developed for wing in ground effect (WIGE) craft and high-speed marine vehicles (planing craft) is carried out. However, the overview only leads to a finding that the longitudinal stability of a lifting surface over wavy ground effect is not entirely established. Taking this fact into account, the analysis of the model is proposed for a WIGE craft configuration. A simplification is adopted considering heave motion only in the modelling of oscillation. The simplification is made to thoroughly capture the effect of oscillation toward dynamic stability of the vehicle. To support the model verification, a numerical simulation followed by a semi-empirical design method was adopted to produce aerodynamic data, both in two-dimensional and three-dimensional domains, respectively. The results show that the combination of underpinning parameters, i.e. ride height, frequency and amplitude of oscillation, remarkably influence the aerodynamics. The characteristics in aerodynamics affect the production of stability derivatives and eventually stability behaviour of the chosen configuration. Some patterns in the results are identified but there also some data that show the peculiarity. Thus further investigation is needed.
Keywords: Aerodynamics; Stability derivatives; Dynamic stability; Oscillation